The role of microRNA in the development of liver diseases. Part 1 - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2023)
The scientific review shows the role of miRNA in the development of liver diseases, namely: acute liver failure, non-alcoholic fatty liver disease. To write the article, information was searched using the databases Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library, CyberLeninka. The authors indicate the importance of some miRNAs in the development of liver diseases. It was established that the development of acute liver failure is associated with a significant increase in the concentration of miR-21, miR-122, miR-221 and miR-192 in blood serum. The authors present the features of changes in miRNA content in acute liver failure in children. It is stated that drug-induced acute liver failure is accompanied by an increase in the concentration level of miR-122, miR-1246, miR-4270, miR-4433, miR-4463, miR-4484, miR-4532, pre-miR-4767 and a decrease in the concentration level miR-455-3p, miR-1281 and pre-miR-4274 in serum. MicroRNAs miR-224-5p, miR-320a, miR-449a and miR-877-5p regulate the process of metabolizing acetaminophen by inhibiting enzymes (CYP3A4, HNF1A, HNF4A and NR1I2). The authors demonstrated that transfection of exogenous miR-224-5p, miR-320a, miR-449a and miR-877-5p into HepaRG cells protects them from the toxic effect of acetaminophen. The scientists demonstrated that patients with non-alcoholic steatohepatitis had more than two-fold increased concentrations of miR-19a and miR-19b, miR-122, miR-125b, miR-192 and miR-375 in their blood serum. It is emphasized that overexpression of miR-122 is associated with high activity of alanine aminotransferase. Thus, the association of micro-RNA generation with the development of liver diseases has become the goal of research by scientists around the world in recent years. The development of acute liver failure is associated with a significant increase in the concentration of miR-21, miR-122, miR-221 and miR-192 in blood serum. A high level of miR-27b-3p, miR-122-5p, miR-192-5p, miR-1290 in blood serum is a highly diagnostic marker of non-alcoholic fatty liver disease. Therefore, microRNAs play an important role in the development of acute liver failure and non-alcoholic fatty liver disease and can be used as diagnostic and prognostic criteria, which, in the future, may contribute to increasing the effectiveness of therapy.